Employment duration and resistance to wage reductions: Experimental evidence - Michael C. Burda; Werner Güth; Georg Kirchsteiger; Harald Uhlig (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
One of the long-standing puzzles in economics is why wages do not fall sufficiently in recessions so as to avoid increases in unemployment. Put differently, if the competitive market wage declines, why don't employers simply force their employees to accept lower wages as well? As an alternative to reviewing statistical data, we have performed an experiment with a lower competitive wage in the second phase of an employment relationship that is known to both parties. The experiment casts two subjects in the highly stylized roles of employer and employee. Our hypothesis is that employers will not lower wages correspondingly and that employees will resist such wage cuts. We find at most mild evidence for resistance to wage declines. Instead, the experimental results can be more fruitfully interpreted in terms of an 'ultimatum game', in which surplus between employers and employees is shared. In this view, wages and their lack of decline are simply the mechanical tool for accomplishing this split.
urn:nbn:de:kobv:11-10060500
Keywords: C72; C78; C91; C92; E24; J31; J41; J52; 330; ultimatum game; wage flexibility; wage ratchet effect; wage bargaining; labour market; fair wages